Pengembangan Kapasitas Kelembagaan Desa Tangguh Bencana (Destana) di Kabupaten Magelang - Mulajaya, R. Permadi; Christiani, Charis (LPPM Institut Pendidikan Nusantara Global, 2024)
Development of institutional capacity in disaster management in Magelang Regency through the Disaster Resilient Village (Destana). The number of disasters that occurred in Magelang Regency in 2022 was 624 disaster events consisting of strong winds or tornadoes, landslides, house fires, forest or land fires, floods and volcanoes. The aim of this research is to analyze the Institutional Capacity Development Policy through Disaster Resilient Villages (Destana) in Magelang Regency. The research methodology uses qualitative methods with data collection techniques through observation, interviews and documentation. The research results found that institutional strengthening in the Destana program was achieved by establishing a Village Disaster Risk Reduction Forum (PRB). This forum has been formed since 2015 and is called